PENGARUH PENERAPAN ETIKA BISNIS ISLAM TERHADAP SISTEM JUAL-BELI DI PASAR TRADISIONAL(Studi Kasus pada Pasar Caplek di Kecamatan Majenang, Kabupaten Cilacap, Jawa Tengah) - Muhammad Ngasifudin; Dede Kurnia; Eka Putri Purwanti; Eni Ma’arifah (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2023)
Business ethics in buying and selling things that must be prioritized, it can't be separated from business ethics, many previous studies have shown a positive relationship between business ethics and trade success, the greater awareness of traders in ethics in business determines the importance of linking factors ethics in business, this study analyzes how much influence Islamic business ethics has in buying and selling at the Majenang Caplek Market. The type of research used is field research with quantitative methods using normative and sociological approaches. The subjects of this research are all traders who are in the Caplek market. The sample of respondents in this study was 30 people with the method of spreading by simple random sampling, which was carried out randomly without regard to the existing strata in the population. The results of this study found that there is a positive influence between the application of Islamic business ethics and the buying and selling system in the Majenang Caplek market with the regression equation Y: 2.713 + 0.470 X, it can be interpreted that the Islamic business ethics variable (X) has a significant effect on the selling system. buy at the Majenang Caplek market